Global cyber security labor shortage and international business risk - Christiansen, Bryan, 1960-; Piekarz, Agnieszka, 1990- (IGI Global, 2019)
"This book explores the current cybersecurity labor crisis and its future effect on global business risk and security. It also covers the different issues associated with this worldwide dilemma and potential solutions"--